A case of pancreaticoduodenectomy and partial hepatic resection as repeat cytoreductive surgery for recurrent pseudomyxoma peritonei - Kenya Yamanaka (SpringerOpen, 2021)
Abstract Background For recurrent pseudomyxoma peritonei (PMP), repeat cytoreductive surgery (CRS) with or without hyperthermic intraperitoneal chemotherapy (HIPEC) can provide survival benefits if patients are carefully selected. We describe a case of pancreaticoduodenectomy and partial liver resection (HPD) as the repeat CRS for a recurrent tumor that infiltrated the pancreatic head around the hepatic hilum. This is the first report of HPD for recurrent PMP. Case presentation The patient was a 58-year-old male without comorbidities. In 2001, he was diagnosed with PMP at the time of laparoscopic cholecystectomy. In 2004, CRS, including total peritoneal resection, pyloric gastrectomy, splenectomy, and right hemicolectomy with HIPEC was performed (peritoneal cancer index (PCI) = 28). In 2008, the first repeat CRS with HIPEC was performed (PCI = 14). In 2016, fourth repeat CRS, including partial hepatectomy with HIPEC for recurrence of the round ligament of the liver, was performed. In 2017, a tumor of 5 cm in size was observed from the hepatic hilum to the pancreatic head, which infiltrated the main pancreatic duct. Other tumors 2 cm in size were observed (PCI = 7). We performed the fifth repeat CRS, including HPD. The adhesions of the small intestine from around the liver to the lower abdomen were detached for the reconstruction of pancreatojejunostomy and cholangiojejunostomy. The uncinate approach was applied for the pancreatic head resection because it was difficult to identify the cranial part of the pancreas due to adhesions in the hepatoduodenal ligament and the omental bursa. We approached to the origin of the extrahepatic Glissonean pedicle by resecting a part of the liver around the hepatic hilum using transhepatic hilar approach. A complete cytoreduction was achieved. The postoperative pathological diagnosis was a recurrence of PMP, which is equivalent to peritoneal mucinous carcinomatosis. He was discharged on the 22nd postoperative day without major postoperative complications. The patient survived without recurrence four years after HPD. Conclusions Even for recurrence around the hepatic hilum and the pancreatic head, repeat CRS can be safely performed by applying the techniques of hepatobiliary pancreatic surgery.